Classifying the causes of perinatal death - Allanson, Emma; Tunçalp, Özge; Gardosi, Jason; Pattinson, Robert C; Erwich, Jan Jaap HM; Flenady, Vicki J; Frøen, J Frederik; Neilson, James; Chou, Doris; Mathai, Matthews; Say, Lale; Gülmezoglu, Metin (Bulletin of the World Health Organization, 2016)
There continues to be slow progress in preventing stillbirths. It is estimated that globally, more than 2 million stillbirths occur each year, adding to 2.9 million neonatal deaths. Ending preventable perinatal deaths is high on the international public health agenda. In countries with the highest mortality burden, limited or non-existent vital registration and medical records mean that perinatal deaths are often not recorded. Thus the first step in addressing high perinatal mortality is the accurate capture and classification of the causes of those deaths across all settings. The World Health Organization (WHO) is developing a system to enable comparisons within and between diverse settings, including low-, middle- and high-income countries. This will allow benchmarking and the identification of trends, gaps and modifiable factors and help to focus local and global efforts on prevention. Using the coding rules of the 10th revision of the International classification of diseases and related health problems (ICD-10), WHO, in collaboration with partners, has developed The WHO application of ICD-10 to perinatal deaths: ICD-perinatal mortality.